The endeavors of Sheikh Muhammad al-Khal to preserve the biography of Kurdish scholars and their scientific efforts A review study - Majeed, Prof. Dr. Kamran Orahman; Al-Mufarji, Prof. Dr. Afrah Hamid Abdulhassan (Sulaimani Journal for Humanities, 2023)
Knowledge and scholars have a great status, as the word “knowledge” and its derivatives are mentioned in the Holy Qur’an more than eight hundred and fifty times, in addition to the fact that the first word revealed from it commanded recitation, and knowledge was mentioned in the first surah that was revealed. We also find that the Holy Qur’an recorded the endeavors and efforts of the prophets and preachers, and in light of that, an explanation The endeavors and scientific services of scholars fall within this framework, as it is acceptable and even recommended work. On this basis, people preferred the path of knowledge and respected those who practiced it, and due to the keenness of Islamic societies and their love for this virtue, no era or Egypt has been without the best centuries, and to this day, there are venerable scholars and sincere preachers who were keen to explain the religion and clarify its issues with all honesty and sincerity.